Mental Wellbeing Impact Assessment (MWIA) in the workplace. Issue 3 (18th September 2017) - Burford, Charlotte; Davey, Silvia; Knight, Alec; King, Sadie; Cooke, Anthea; Coggins, Tony
Abstract : Purpose: The Mental Wellbeing Impact Assessment (MWIA) is an evidence-based tool that guides decision makers, such as policy makers and service managers, about the potential impacts of a new programme or policy change. It was initially used in urban regeneration but has subsequently been used in housing, children's centres and education. The purpose of this paper is to report, for the first time, on the strengths and weaknesses of using the MWIA in the workplace. Design/methodology/approach: Feedback was collected from staff who participated in stakeholder workshops as part of the MWIA process at two different public sector organisations. Findings: The MWIA can be used as an effective workplace assessment tool and is valuable as both a diagnostic tool and as an intervention in its own right. The MWIA generates tailored action plans focussed on addressing the organisation or team-specific issues. The weaknesses of the MWIA in the workplace are mainly focussed around management cooperation and commitment to the process which should be screened for prior to engaging in the full stakeholder workshop. Originality/value: This is the first report of MWIA's use in the workplace but suggests that it is a useful tool which can be used to support workplace wellbeing, especially in relation to a policy or organisational change. Further studies should be carried out to fully understand the impact of the MWIA in the workplace.